Written Contributions of Selected Accounting Practitioners, Volume 2 (Book). - McNelis, Leslie L.; Burns, Thomas J. (The Accounting Review, 1980)
Reviews the book "Written Contributions of Selected Accounting Practitioners," vol. 2, by Paul Grady.